2023
DOI: 10.1038/s41598-023-38028-6
|View full text |Cite
|
Sign up to set email alerts
|

Response of seed yield and biochemical traits of Eruca sativa Mill. to drought stress in a collection study

Abstract: Drought tolerance is a complex trait in plants that involves different biochemical mechanisms. During two years of study (2019–2020), the responses of 64 arugula genotypes to drought stress were evaluated in a randomized complete block design with three replications under field conditions. Several metabolic traits were evaluated, i.e. relative water content, photosynthetic pigments (chlorophyll and carotenoids), proline, malondialdehyde, enzymatic antioxidants (catalase, ascorbate peroxidase, and peroxidase), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
3
1
0
Order By: Relevance
“…Under heavy metal stresses, flavonoids enhance the process of metal chelation, which may reduce the level of harmful hydroxyl radicals in plant cells 62 . In the present study, increasing drought stress intensity led to an increase in TPC and TFD, which were consistent with the previous reports in Carthamus tinctorius 63 and Eruca sativa 64 . Also, the increase in Cu concentrations up to Cu 400 , resulted in an increase in TPC and TFD.…”
Section: Discussionsupporting
confidence: 93%
“…Under heavy metal stresses, flavonoids enhance the process of metal chelation, which may reduce the level of harmful hydroxyl radicals in plant cells 62 . In the present study, increasing drought stress intensity led to an increase in TPC and TFD, which were consistent with the previous reports in Carthamus tinctorius 63 and Eruca sativa 64 . Also, the increase in Cu concentrations up to Cu 400 , resulted in an increase in TPC and TFD.…”
Section: Discussionsupporting
confidence: 93%
“…These results may be related to the adequate actions of these antioxidants, which can remove ROS and reduce the harmful effects of stress conditions. These outcomes are consistent with the findings of previous reports in lentil [41,67] and other species [38,68,69]. In addition, we observed a significant correlation between TPC and TAA under high-temperature stress conditions.…”
Section: Discussionsupporting
confidence: 93%
“…As a protective mechanism, plants deploy antioxidant enzymes such as CAT, APX, and SOD as their primary defense to scavenge H 2 O 2 with different mechanisms and suppress its toxic impacts [37]. Our study observed heightened activities of antioxidant enzymes in nearly all tolerant and moderately tolerant lentil accessions, as a response to the stresses of high temperature and drought, which was in agreement with the outcomes of other investigations [38][39][40][41][42]. Under adverse environmental conditions, complex antioxidant enzyme activities play a critical role in overcoming uncontrolled reactive oxygen species generation and protecting plants from oxidative damage [23].…”
Section: Discussionsupporting
confidence: 92%
“…The reaction of APX included 50 mL of enzyme extract, 2 mL of ascorbic acid (5 mM), 5 mL of 50 mM phosphate buffer (pH 7.0), and 10 μL of H 2 O 2 (0.5 mM). The reaction was analyzed at 290 nm for 3 min [ 40 ].…”
Section: Methodsmentioning
confidence: 99%